(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
Aeroflot PJSC is the largest and oldest air carrier in our country. Throughout its existence, Aeroflot has played a key role in air transportation on the territory of our country and on foreign routes. Today, the company retains the status of the most profitable, efficient and innovative airline in our country. The aim of this work is to analyze key performance indicators of PJSC Aeroflot based on reporting data.